Controversial role of toll-like receptor 4 in adult stem cells - Zeuner, Marie; Bieback, Karen; Widera, Darius (Stem cell reviews and reports, 2015)
Adult or somatic stem cells are tissue-resident cells with the ability to proliferate, exhibit self-maintenance as well as to generate new cells with the principal phenotypes of the tissue in response to injury or disease. Due to their easy accessibility and their potential use in regenerative medicine, adult stem cells raise the hope for future personalisable therapies. After infection or during injury, they are exposed to broad range of pathogen or damage-associated molecules leading to changes in their proliferation, migration and differentiation. The sensing of such damage and infection signals is mostly achieved by Toll-Like Receptors (TLRs) with Toll-like receptor 4 being responsible for recognition of bacterial lipopolysaccharides (LPS) and endogenous danger-associated molecular patterns (DAMPs). In this review, we examine the current state of knowledge on the TLR4-mediated signalling in different adult stem cell populations. Specifically, we elaborate on the role of TLR4 and its ligands on proliferation, differentiation and migration of mesenchymal stem cells, hematopoietic stem cells as well as neural stem cells. Finally, we discuss conceptual and technical pitfalls in investigation of TLR4 signalling in stem cells.
Gesehen am 21.02.2018